3-point shot performance analysis - Deng, F.; Guo, D. -W.; Zhang, Z. -M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The results of this study indicate that world top teams hold high 3FG%, and that interior strength continues to be the determinant of a powerful team. Only when interior strength of both sides match, 3-point shot maters. Comparing with top teams, the weaker the team, the more 3FGA; and the higher 3FGM proportion in total FGM; and the lower the 3FG%. Including 3-point shot in basketball rules didn't change the fundamental law of basketball. 2-point shots are still the most important source of scoring. Under specific circumstance 3-point shot is effective. But a team depends too much on long range offences always has instable performance and can't be world top team. This study suggests that CBA League should adjust its strategy. More efforts are needed to improve the three point shots Scoring Efficiency (Points/Shot), which is to reduce the attempts and to improve the 3-point field goal percentage.